Understanding the Adoption Factors Influence on the Use of Intelligent Travel Assistant (ITA) for Eco-Tourists: An Extension of the UTAUT - Noppadol Phaosathianphan (2020)
© 2019 World Scientific Publishing Company. The objective of this research is to investigate the antecedent factors involving eight variables, i.e. ease of use, trust, enjoyment, design, usefulness, quality, safety and empathy, which influence user acceptance of the intelligent travel assistant (ITA), thus they are formulated into a research model and hypothesis according to wide and deep exploration about the theories of travel and tourism. The technologies used were the VPA, IPA, AI, IoT, technology acceptance theories and related literature. The data collection used online questionnaires for the survey through social media promotion online, i.e. Facebook and Line. The data analysis was conducted with the 299 eco-tourists via the descriptive statistics, that is, percentages and standard deviations (S.D.) through the program of PASW Statistics v.18.0.0. The statistical inferential analysis has used the measurement model and the structural model through employing the program of SmartPLS v.3.2.8. Their results led to recognizing the ITA user acceptance containing firstly the external factors, which involve the ease to use, the trust, the enjoyment, and the design. Secondly, the internal factors included the usefulness, and the quality. Thirdly, the direct factor is the empathy. Finally, the results of this study could be applied for implementation and assessment of ITA in the future.